An Empirical analysis of an e-government system for economic growth in ECOWAS countries - Afees Oluwashina, Noah; Oladipo Olalekan, David (Penerbit Universiti Kebangsaan Malaysia, 2024)
In many ECOWAS countries, the decision-making process for public service delivery has long remained shrouded in secrecy, rendering the general public largely uninformed. Integrating information and communication technology (ICT) into public service delivery seeks to break these barriers. This study, therefore, investigates the impact of e-governance on economic growth among ECOWAS countries, with the specific objectives of examining the effect of four components of e-governance as well as other postulated determinants on economic growth. By employing annual data across 16 ECOWAS countries spanning from 2003 to 2021, using system generalised method of moment (SGMM) and panel-corrected standard error (PCSE) techniques. The results from the PCSE and SGMM estimations show that e-governance positively influences economic growth among ECOWAS countries both in the long- and short-run. Furthermore, the study identifies the significant influence of various control variables on economic growth, persisting in both short and long-run analyses, except for the labour force variable in the short run. This underlines the intrinsic correlation between e-governance and economic growth. Consequently, it becomes imperative for stakeholders within the sub-region to meticulously link investments in e-governance with measurable economic growth outcomes. By doing so, these investments can substantiate expansive initiatives in public service delivery, while simultaneously bridging the historical gap of opacity that has separated citizens from effective government management.